Monitoreo de la regeneración natural de especies arbóreas y arbustivas del matorral andino afectado por incendios forestales en el Parque Universitario “Francisco Vivar Castro” - Giron Erazo, Mitzi Gorety (2023)
Natural regeneration is a dynamic process that re-establishes ecosystems naturally after a disturbance. The research was carried out in an matorral andino affected by forest fires in the Francisco Vivar Castro University Park. The objectives were to describe the changes in natural regeneration and the effect of environmental variables on its abundance. The regeneration categories evaluated were plantula, brinzal and latizal. To determine the changes in regeneration over time, abundance, species, heights and diameters at 1.30 m were measured in permanent plots, especially for latizales, which were used to calculate composition, diversity, structural parameters, mortality, survival and recruitment. To evaluate the effect of environmental variables on the abundance of regeneration, this value was correlated with data on slope, soil cover, P. arachnoideum cover, canopy openness and depth of the organic layer. In the period evaluated, the natural regeneration did not show significant changes in diversity, composition and structural parameters. Growth was evident in all categories, both in shrubs and trees, but without being significant. There was recruitment of new individuals in the plantula category, 3 trees and 8 shrubs, with Baccharis sp.1 and Dendrophorbium scytophyllum being the species with the greatest contribution. Survival in shrubs and trees was adequate with 91 %. Mortality was present in brinzal and in few species. Environmental variables did not show a significant association with regeneration, except for slope and soil cover that expressed a strong negative association with the latizal category. Changes in natural regeneration were present but not significant; and the environmental variables analyzed did not explain the abundance of regeneration, demonstrating the preference of species to sites with specific biophysical conditions.